Primary hepatic angiosarcoma with noncirrhotic portal hypertension: A case report - Wu, Xuwei; Yu, Xia; Gan, Qiaorong; Wang, Bin; Lin, Zhaowang; Shi, Yu; Huang, Zuxiong (Frontiers in Oncology, 2023)
Background: Primary Hepatic angiosarcoma (PHA) is a rare type of malignant tumor with mesothelial tissue origin in the liver. The diagnosis of PHA relies on pathology and is frequently misdiagnosed as multiple hepatic hemangioma by imaging. Noncirrhotic portal hypertension is a relatively rare pathological manifestation. There have been few reports in the current literature that PHA is an uncommon cause of noncirrhotic portal hypertension. Case summary: A 36-year-old young male was admitted with abnormal liver function, suspecting drug-induced liver injury (DILI) and multifocal hepatic hemangioma as the initial manifestation. The biopsy findings showed features of noncirrhotic portal hypertension (NCPH) and was eventually diagnosed to have multifocal hepatic angiosarcoma. Conclusion: Patients with PHA may represent histologic appearance of NCPH in the background liver due to injury to the hepatic sinusoids. It is necessary to consider the possibility of unsampled vascular malignancy when hepatic masses are identified on imaging and histology is consistent with PHA.